1969
DOI: 10.1002/jez.1401700303
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ribosomal RNA synthesis in initiation of Wolffian lens regeneration

Abstract: Tissue engaged in the transformation of iris into lens, triggered by lens removal in the adult newt (Triturus viridescens), was labeled in vitro with 14c-uridine, and the sedimentation profiles of RNA synthestized by the tissue were studied in sucrose density gradients. The radioactivity in the 18s and 285 areas, which is insignificant in the normal iris, increases significantly during 2 to 10 days after lens removal, and subsequently retains a high level until the completion of lens regeneration. These data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The nuclei of the macrophages in the present study also contained coarsely clumped chromatin, but a similar chromatin configuration was also found in normal iris epithelial cells. Dispersed chromatin was not observed in nuclei of iris epithelial cells until 6 days after lentectomy a t a time when nucleolar activation and rRNA synthesis have been initiated (Dumont et al, 1970;Reese et al, 1969). Dumont and Yamada (1972) also found small, electron-dense concretions associated with the plasma membrane of iris epithelial cells 8 days after lentectomy.…”
Section: Resultsmentioning
confidence: 93%
“…The nuclei of the macrophages in the present study also contained coarsely clumped chromatin, but a similar chromatin configuration was also found in normal iris epithelial cells. Dispersed chromatin was not observed in nuclei of iris epithelial cells until 6 days after lentectomy a t a time when nucleolar activation and rRNA synthesis have been initiated (Dumont et al, 1970;Reese et al, 1969). Dumont and Yamada (1972) also found small, electron-dense concretions associated with the plasma membrane of iris epithelial cells 8 days after lentectomy.…”
Section: Resultsmentioning
confidence: 93%
“…Two days after lentectomy, REESE et al (1969) reported increased incorporation of 14C-uridine into the 18 Sand 28 S ribosomal RNA and 4 S RNA isolated by sucrose density gradient centrifugation from the RNA obtained by phenol extraction of homogenates from dorsal iris. These changes of nucleolar activation take place by 2 days after lentectomy and become even more prominent after 4 days providing morphologic evidence for the production of ribosomal RNA in the nucleolus.…”
Section: Cytologic and Macromolecular Eventsmentioning
confidence: 99%
“…Later, Dumont et al (1970) described the changes in the nucleoli. These increase in number and become enlarged and more granular as rRNA synthesis is activated (Reese et al, 1969). Yamada and Dumont (1972) investigated further the appearance and activity of the macrophages t h a t invade the iris epithelium and phagocytize melanosomes during depigmentation of the iris epithelial cells.…”
mentioning
confidence: 99%